2013
DOI: 10.1155/2013/636585
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Anemia and Associated Factors in Child Bearing Age Women in Riyadh, Saudi Arabia

Abstract: Objective. To determine the prevalence and risk factors for anemia in child bearing age women in Riyadh, Saudi Arabia. Design. Cross-sectional survey was conducted using two-stage cluster sampling. 25 clusters (primary health care centers (PHCC)) were identified from all over Riyadh, and 45–50 households were randomly selected from each cluster. Eligible women were invited to PHCC for questionnaire filling, anthropometric measurements, and complete blood count. Blood hemoglobin was measured with Coulter Cellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
53
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(71 citation statements)
references
References 14 publications
(9 reference statements)
8
53
2
Order By: Relevance
“…According to the WHO classification, the cutoffs for anemia are 12 g/dL for females and 13 g/dL for males [8]. In Saudi Arabia, Alquaiz [9] found that 40% of women of child bearing age suffered from anemia in the city of Riyadh. These authors also found a mean HGB of 12.35 (±1.80) g/dL.…”
Section: Discussionmentioning
confidence: 99%
“…According to the WHO classification, the cutoffs for anemia are 12 g/dL for females and 13 g/dL for males [8]. In Saudi Arabia, Alquaiz [9] found that 40% of women of child bearing age suffered from anemia in the city of Riyadh. These authors also found a mean HGB of 12.35 (±1.80) g/dL.…”
Section: Discussionmentioning
confidence: 99%
“…In a survey of 969 women of childbearing age in the KSA, Alquaiz et al reported a 40% prevalence of anemia (Hb < 12 g/dL) [83]. An earlier study by Al-Quaiz et al of 87 anemic and 203 non-anemic women in the KSA found the risk of IDA diagnosis to increase 2–4 fold due to the low frequency of eating meat, vegetables, and/or drinking juices with vitamin C [84].…”
Section: Prevalence Of Micronutrient Deficiencies In the Middle Eastmentioning
confidence: 99%
“…Moreover, a major problem in Arab countries is to determine "normal healthy individuals" due to the high prevalence of hemoglobin (Hb) disorders, iron deficiency anemia and viral infections [3][4][5]. It is important to recognize that reference ranges in your laboratory may be different; when interpreting results from patients in your laboratory, you must use your own local reference ranges.…”
Section: Introductionmentioning
confidence: 99%